Inmenso estrecho: Obstacles to Achieving Post-inmigration Identity Change in Spanish Short Fiction. - Ryan Prout. (Tejuelo: Didáctica de la Lengua y la Literatura)
This article reads a selection of short stories from the Inmenso estrecho collection alongside work by psychologists of immigration. Salman Akhtar has systematised the adjustment process which a migrant must go through if he or she is to feel well adapted to his or her new culture and society. This process depends on a number of support factors being in place. Where these are not available the process of adaptation can be stymied and the article connects the difficulties of the fictional immigrants in the stories with the poor adaptations studied by Akhtar in his clinical work.